Delay-efficient 4:3 counter design using two-bit reordering circuit for high-speed Wallace tree multiplier - Madaka Venkata Subbaiah; Galiveeti Umamaheswara Reddy (International Journal of Electrical and Computer Engineering (IJECE), 2023)
In many signal processing applications, multiplier is an important functional block that plays a crucial role in computation. It is always a challenging task to design the delay optimized multiplier at the system level. A new and delay-efficient structure for the 4:3 counter is proposed by making use of a two-bit reordering circuit. The proposed 4:3 counter along with the 7:3 counter, full adder (FA), and half adder (HA) circuits are employed in the design of delay-efficient 8-bit and 16-bit Wallace tree multipliers (WTMs). Using Xilinx Vivado 2017.2, the designed circuits are simulated and synthesized by targeting the device ‘xc7s50fgga484-1’ of Spartan 7 family. Further, in terms of lookup table (LUT) count, critical path delay (CPD), total on-chip power, and power-delay-product (PDP), the performance of the proposed multiplier circuit is compared with the existing multipliers.